Codelivery of GRP78 siRNA and docetaxel via RGD-PEG-DSPE/DOPA/CaP nanoparticles for the treatment of castration-resistant prostate cancer - Zhang X; He Z; Xiang L; Li L; Zhang H; Lin F; Cao H (Dove Medical Press, 2019)
Xiangyu Zhang,1,* Zelai He,2,* Longquan Xiang,1 Liang Li,1 Haiyan Zhang,1 Fanzhong Lin,1 Hongying Cao11Department of Pathology, Jining First People’s Hospital, Jining Medical University, Jining 272000, People’s Republic of China; 2Department of Radiation Oncology, The First Affiliated Hospital of Bengbu Medical University & Tumor Hospital Affiliated to Bengbu Medical University, Bengbu 233004, People’s Republic of China   *These authors contributed equally to this work Background: Castration-resistant prostate cancer (CRPC) accounts for the majority of prostate cancer deaths, and patients with CRPC are prone to developing drug resistance. Therefore, there is a need to develop effective therapeutics to treat CRPC, especially drug-resistant CRPC. Although various nanoparticles have been developed for drug or gene delivery and control release, approaches to reproducibly formulate the optimal treatment with nanoparticles that could effectively target CRPC and bone metastasis remain suboptimal. Recently, codelivery of a chemotherapeutic agent and a small interfering RNA (siRNA) has become a promising strategy for the treatment of drug-resistant prostate cancer.Methods: In a previous study, we prepared a novel RGD-PEG-DSPE/CaP nanoparticle as an effective and biocompatible drug and gene delivery system. In this study, we further modify the nanoparticle to obtain the LCP-RGD nanoparticle, which contains a calcium phosphate (CaP) core, dioleoyl phosphatidic acid (DOPA) and RGD modified poly(ethylene glycol)-conjugated distearoyl phosphatidylethanolamine (RGD-PEG-DSPE). This drug delivery system was used for codelivery of GRP78 siRNA and docetaxel (DTXL) for the treatment of the PC-3 CRPC.Results: The nanoparticles contain the CaP core, which can effectively compress the negatively charged siRNA, while the DOPA and RGD-PEG-DSPE component can effectively carry DTXL. The arginine-glycine-aspartic acid (RGD) segment can target the prostate cancer site, as the cancer site is neovascularized. This novel nanoparticle has good stability, excellent biocompatibility, high drug and siRNA loading capacity, and an in vitro sustainable release profile.Conclusion: Codelivery of DTXL and GRP78 siRNA has enhanced in vitro and in vivo anti-prostate cancer effects which are much greater than using free DTXL and free GRP78 siRNA together. Our study also indicated that codelivery of DTXL and GRP78 siRNA have an in vitro and in vivo combinational anti-prostate cancer effect and also could effectively sensitize the cell-killing effect of DTXL; this method may be especially suitable for drug-resistant CRPC treatment.Keywords: codelivery, docetaxel, RANK, siRNA, nanoparticles